2021
DOI: 10.3390/s21186012
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission-Based Condition Monitoring and Remaining Useful Life Prediction of Hydraulic Cylinder Rod Seals

Abstract: The foremost reason for unscheduled maintenance of hydraulic cylinders in industry is caused by wear of the hydraulic seals. Therefore, condition monitoring and subsequent estimation of remaining useful life (RUL) methods are highly sought after by the maintenance professionals. This study aimed at investigating the use of acoustic emission (AE) sensors to identify the early stages of external leakage initiation in hydraulic cylinders through run to failure studies (RTF) in a test rig. In this study, the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Pedersen et al [31] conducted a study to determine the early stages of external leakage initiation in hydraulic cylinders through Run-To-Failure (RTF) studies of PolyTetraFluoroEthylene (PTFE) seals in a test rig. An accelerated leakage initiation process was conducted by generating longitudinal scratches on the piston rod.…”
Section: Mechanical Accelerated Testing Of Hydraulic Sealsmentioning
confidence: 99%
“…Pedersen et al [31] conducted a study to determine the early stages of external leakage initiation in hydraulic cylinders through Run-To-Failure (RTF) studies of PolyTetraFluoroEthylene (PTFE) seals in a test rig. An accelerated leakage initiation process was conducted by generating longitudinal scratches on the piston rod.…”
Section: Mechanical Accelerated Testing Of Hydraulic Sealsmentioning
confidence: 99%
“…From the RTF tests conducted a comparison of the time and frequency domain features were conducted, and it was observed that the RMS feature was the most suited for use as condition monitoring indicators to identify wear of piston rod seals (Pedersen et al 2021). Therefore, in this study, the RMS feature was used to develop the ARIMA model.…”
Section: Arima Model Using the Rms Featurementioning
confidence: 99%
“…To classify the severity of fluid leakage, an optimization deep belief network (DBN) combined with the Complete Ensemble Empirical Model Decomposition with Adaptive Noise (CEEMDAN) was used and classification accuracy up to 93 % was achieved. (Pedersen et al 2021), performed run-to-failure tests at different pressure and speed conditions on a hydraulic test rig to understand the AE features that can be evaluated to determine fluid leakage initiation. RMS features were proposed as potential condition monitoring indicators to understand fluid leakage initiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The features are selected to characterize the system dynamics during transient and steady-state operation and then combined to produce a condition indicator. In (Pedersen, Schlanbusch, Meyer, Caspers, & Shanbhag, 2021), acoustic emission (AE) sensors are used to identify the early stages of external leakage initiation in hydraulic cylinders. The impact of sensor location and rod speeds on the AE signal were investigated using both time-and frequency-based features.…”
Section: Introductionmentioning
confidence: 99%